Emergency department characteristics and capabilities in Bogotá, Colombia (2015)
Background: Emergency departments (EDs) are a critical, yet heterogeneous, part of international emergency care. The National ED Inventories (NEDI) survey has been used in multiple countries as a standardized method to benchmark ED characteristics. We sought to describe the characteristics, resources, capabilities, and capacity of EDs in the densely populated capital city of Bogotá, Colombia. Methods: Bogotá EDs accessible to the general public 24/7 were surveyed using the 23-item NEDI survey used in several other countries (www.emnet-nedi.org). ED staff were asked about ED characteristics with reference to calendar year 2011. Results: Seventy EDs participated (82 % response). Most EDs (87 %) were located in hospitals, and 83 % were independent hospital departments. The median annual ED visit volume was approximately 50,000 visits. Approximately 90 % (95 % confidence interval (CI) 80–96 %) had a contiguous layout, with medical and surgical care provided in one area. Almost all EDs saw both adults and children (91 %), while 6 % saw only adults and 3 % saw only children. Availability of technological and consultant resources in EDs was variable. Nearly every ED had cardiac monitoring (99 %, 95 % CI 92–100 %), but less than half had a dedicated CT scanner (39 %, 95 % CI 28–52 %). While most EDs were able to treat trauma 24/7 (81 %, 95 % CI 69–89 %), few could manage oncological (22 %, 95 % CI 13–34 %) or dental (3 %, 95 % CI 0–11 %) emergencies 24/7. The typical ED length-of-stay was between 1 and 6 h in 59 % of EDs (95 % CI, 46–70 %), while most others reported that patients remained for >6 h (39 %). Almost half of respondents (46 %, 95 % CI 34–59 %) reported their ED was over capacity. Conclusions: Bogotá EDs have high annual visit volumes and long length-of-stay, and half are over capacity. To meet the emergency care needs of people in Bogotá and other large cities, Colombia should consider improving urban ED capacity and training more emergency medicine specialists capable of efficiently staffing its large and crowded EDs. © 2015, Bustos et al.